Estimation of unsaturated hydraulic conductivity function using extrapolated saturated front widths of line source field dripper - OJHA, ROHIT PRATAP; CHANDRA, HARISH; TOMAR, ARVIND SINGH; MISHRA, RAJAT; KUMAR, ABHINAV; ARORA, SANJAY (Journal of Soil and Water Conservation, 2024)
Unsaturated hydraulic conductivity plays a vital role in understanding and managing water movement through porous media. Accurate estimation of this property is crucial for various applications, including soil moisture dynamics, groundwater recharge, and hydrological modelling. The line source field dripper method for in-situ measurement of unsaturated hydraulic conductivity using extrapolated steady-state saturated front widths is evaluated. The saturated hydraulic conductivity values obtained by line-source field dripper method with extrapolated saturated front widths are lower than the values obtained by point-source field dripper method of line source field dripper method for cultivated recently tilled normal soil, cultivated untilled normal soil, cultivated recently tilled sodic soil and uncultivated untilled sodic soil. The values are higher than the values obtained by inverse auger hole, constant head permeameter, and infiltrometer methods. The use of extrapolated saturated front widths gave the best values of hydraulic conductivity. Extrapolated saturated front widths could give more realistic value of steady state saturated front width for the estimation of conductivity function. The saturated hydraulic conductivity (Ks) calculated by LSFDM with routine saturated front data were obtained as 4.08, 3.18, 1.77 and 0.426 cm/hr, while with extrapolated widths, its value for Cultivated Recently Tilled Normal Soil (CRTNS), Cultivated Untilled Normal Soil (CUTNS), Cultivated Recently Tilled Sodic Soil (CRTSS) and Uncultivated Untilled Sodic Soil (UUTSS) were obtained as 3.29, 2.81, 1.55 and 0.408 cm/hr for, respectively. The Ks values by PSFDM were obtained as 20.20, 8.62, 5.70 and 0.448 cm/hr for CRTNS, CUTNS, CRTSS and UUTSS, respectively. The Ks values obtained with saturated fronts widths were 19.36, 11.64, 12.43 and 4.22% were found lower than the values obtained with extrapolated saturated fronts.